Temporal characteristics of Thomas flairs on the pommel and floor - Prassas, S.; Ariel, G.; Tsarouhas, E. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
To perform successfully on any apparatus, gymnasts must execute skills with creativity and virtuosity. Whereas creativity is demonstrated by introducing new skills, combining existing ones, or adapting skills to different apparatuses, virtuosity is expressed by executing skills with exceptional technique (Prassas et al. 2006). The Thomas Flairs (Fig. 1), originally introduced and performed on the pommel horse, have been adapted on other apparatuses including the floor. Understanding the timing of the different phases of the skill and what effect the different physical characteristics of the two apparatuses may impose on that timing, would be valuable to coaches and gymnasts seeking to improve performance, judges evaluating gymnastic routines, and scientists studying motor skills.